2007
DOI: 10.1007/s00702-007-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CB1 cannabinoid receptor in the anterior cingulate cortex in schizophrenia, bipolar disorder, and major depression

Abstract: The human endogenous cannabinoid system is an appealing target in the investigation of psychiatric disorders. In schizophrenia, endocannabinoids and their receptors are involved in the pathology of the disease. Previous studies reported an increased radioligand binding to cannabinoid receptors 1 (CB(1)) in schizophrenia, both in the dorsolateral prefrontal cortex and in the anterior cingulate cortex (ACC). We analyzed the expression of the CB(1) receptors in the ACC at the protein level using immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 38 publications
2
91
2
Order By: Relevance
“…The possibility that overactive CB 1 receptors might account for the emergence of schizophrenic symptoms has also been challenged. Indeed, although initial postmortem studies showed increased CB 1 binding in cortical areas of schizophrenic patients (Dean et al, 2001;Zavitsanou et al, 2004), more recent measurements of CB 1 mRNA or protein have not confirmed this putative upregulation (Dalton et al, 2011;Koethe et al, 2007;Uriguen et al, 2009), and found instead decreased CB 1 density in the dorsolateral prefrontal cortex (Eggan et al, 2008). Moreover, CB 1 abnormalities have been related to specific schizophrenia subtypes, as suggested by the association of some polymorphisms of the CB 1 receptor Deficient CB 1 activation in social withdrawal A Seillier et al gene CNR1 with the hebephrenic type of schizophrenia (Chavarria-Siles et al, 2008;Ujike et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that overactive CB 1 receptors might account for the emergence of schizophrenic symptoms has also been challenged. Indeed, although initial postmortem studies showed increased CB 1 binding in cortical areas of schizophrenic patients (Dean et al, 2001;Zavitsanou et al, 2004), more recent measurements of CB 1 mRNA or protein have not confirmed this putative upregulation (Dalton et al, 2011;Koethe et al, 2007;Uriguen et al, 2009), and found instead decreased CB 1 density in the dorsolateral prefrontal cortex (Eggan et al, 2008). Moreover, CB 1 abnormalities have been related to specific schizophrenia subtypes, as suggested by the association of some polymorphisms of the CB 1 receptor Deficient CB 1 activation in social withdrawal A Seillier et al gene CNR1 with the hebephrenic type of schizophrenia (Chavarria-Siles et al, 2008;Ujike et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While a significant increase of CB1 density in the prefrontal cortex of depressed suicide victims (375) and of serum AEA levels in patients suffering from minor depression (352) were reported, decreased CB1 density in grey matter (442) and lower levels of endocannabinoids in the serum of patients with major depression and anxiety (351) were also found. Intense exercise has antidepressant effects and increases both AEA and BDNF levels (344), and enhanced endocannabinoid signaling promotes neurogenesis with both antidepressant and anxiolytic effects (350).…”
Section: Mood and Emotionsmentioning
confidence: 99%
“…It should be noted that despite no pathological alteration of mGluR2/3 and mGluR5 binding sites in the present study, the ACC remains highly involved in these pathologies as alterations of various neurotransmitters and their associated receptors have been reported in this brain region. 3,7,[40][41][42] Although our study provides valuable information on these binding sites in psychiatric pathology, additional studies examining binding specifically to membranous mGluR2/3 and mGluR5 and the affinity of novel mGluR2/3-and mGluR5-targeting drugs for these receptors in psychiatric disorders will provide valuable insight into the effectiveness of these drugs in the patient. 33 One confound of postmortem studies in neuropsychiatric disorders, is the presence of comorbid substance abuse, especially alcohol and drug abuse, or at least substantially higher alcohol 43 and illicit drug 44 intake in patients with psychiatric disorders.…”
Section: Limitationsmentioning
confidence: 99%